2009
DOI: 10.1038/npp.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Exposure Alters NMDAR Function in the Bed Nucleus of the Stria Terminalis

Abstract: Chronic alcohol exposure can cause dramatic behavioral alterations, including increased anxiety-like behavior and depression. These alterations are proposed to be due in part to adaptations in the brain regions that regulate emotional behavior, including the bed nucleus of the stria terminalis (BNST), a principal output nucleus of the amygdala. However, to date there have been no studies that have examined the impact of in vivo alcohol exposure on synaptic function in the BNST. In order to better understand ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 49 publications
11
105
1
Order By: Relevance
“…Therefore, it was important to determine whether DA acted on NMDAR of specific composition. Kash et al (2008aKash et al ( , 2009 showed that chronic passive (experimenter-controlled) exposure to alcohol alters the subunit composition of NMDAR throughout the dorsolateral BNST, which includes the ovBNST. We observed that NMDA-EPSC became insensitive to noncompetitive GluN2B antagonists, suggesting a loss of synaptic diheteromeric GluN1/ GluN2B 2 NMDAR (GluN2B non-competitive antagonists being ineffective at triheteromeric GluN1/GluN2A/GluN2B (Hatton and Paoletti, 2005)).…”
Section: Loss Of Glun2b-mediated Nmda-epsc In Cocaine Self-administermentioning
confidence: 99%
“…Therefore, it was important to determine whether DA acted on NMDAR of specific composition. Kash et al (2008aKash et al ( , 2009 showed that chronic passive (experimenter-controlled) exposure to alcohol alters the subunit composition of NMDAR throughout the dorsolateral BNST, which includes the ovBNST. We observed that NMDA-EPSC became insensitive to noncompetitive GluN2B antagonists, suggesting a loss of synaptic diheteromeric GluN1/ GluN2B 2 NMDAR (GluN2B non-competitive antagonists being ineffective at triheteromeric GluN1/GluN2A/GluN2B (Hatton and Paoletti, 2005)).…”
Section: Loss Of Glun2b-mediated Nmda-epsc In Cocaine Self-administermentioning
confidence: 99%
“…Direct examination of ion current through the NMDAR pore has revealed effects consistent with a chronic EtOH-induced upregulation of NMDAR function (Floyd et al 2003;Grover et al 1998). An increase in the component of current mediated by NR2B-containing receptors has also been observed (Floyd et al 2003;Kash et al 2009;Roberto et al 2004b. Interestingly, acute EtOH inhibition of NMDARs in most brain regions is still intact or even increased after chronic in vivo exposure (Floyd et al 2003;Roberto et al 2004b), although a small decrease in inhibition was observed in medial septum/diagonal band neurons (Grover et al 1998).…”
Section: Chronic Ethanol Effects On Glutamatergic Transmission and Glmentioning
confidence: 86%
“…1B,D) (Wills et al 2012). Additionally, chronic ethanol exposure blunted the inhibitory effects of acute in vitro ethanol administration in the vBNST suggesting that NMDARs likely develop tolerance to the acute ethanol effects (Kash et al 2009). This is particularly curious given the key role of GluN2B in ethanol sensitivity of NMDARs in this region coupled with its increased expression after chronic exposure.…”
Section: Ethanol Actions On Nmdar In the Bnstmentioning
confidence: 99%
“…Wills and D.G. Winder levels and increased GluN2B antagonism on NMDAR EPSCs and decay kinetics (Kash et al 2009). These changes are consistent with functional up-regulation of GluN2B from chronic ethanol and it is this increase that likely contributes to enhanced temporal summation of NMDAR EPSCs.…”
Section: Ethanol Actions On Nmdar In the Bnstmentioning
confidence: 99%
See 1 more Smart Citation